Petrophysical and Mechanical Properties of the Piromafo Stone Used in the Built Heritage of Apulia (SE Italy): A Comprehensive Laboratory Study - Gioacchino Francesco Andriani (Geosciences, 2024)
Many historic buildings and monuments on the Salento Peninsula (Apulia, southern Italy) were built from locally quarried Miocene calcarenites belonging to the Pietra Leccese Formation (Late Burdigalian–early Messinian). The main facies consists of a homogeneous and porous biomicrite, pale yellow in colour and fine- to medium-grained, very rich in planktonic Foraminifera and massive or thick-bedded in outcrop. Additionally, there are other facies, among which Piromafo stands out for its aesthetic appearance, enhanced by its greenish-brown or greenish-grey colours. Piromafo occurs in the upper part of the Pietra Leccese Fm. and is represented by a fine- to medium-grained glauconitic and phosphatic biomicrite with macrofossils, especially Bivalves and Gastropods. Despite its important historical use as a building and ornamental material, especially in Roman and Baroque architecture, a research gap exists in the scientific literature describing the properties of the stone and their correlation. Therefore, the aim of this paper is to present a wide range of properties useful in explaining the in situ behaviour and damage susceptibility of the stone in monuments and buildings, but also to assist in selecting preservation treatments and strategies. An overall assessment of the main petrophysical and mechanical properties, especially for restoration/conservation purposes, was performed using both standard and unconventional techniques. Starting with rock fabric inspection, particular attention was given to the relationship between the pore size distribution and the hydraulic and thermal properties of the material. Unconfined compressive strength, flexural strength, and indirect tensile strength were also estimated. The findings reveal a significant correlation between the pore size distribution and the hydraulic and thermal properties of Piromafo, impacting its durability and suitability for use in conservation. Specifically, the thermal properties, influenced by the mineral composition and fabric, indicate the ...